The anti-diabetic effects of metformin are mediated by regulating long non-coding RNA - Chang, Wenguang; Li, Wei; Li, Peifeng (Frontiers in Pharmacology, 2023)
Type 2 Diabetes (T2D) is a metabolic disease with complex etiology and mechanisms. Long non-coding RNA (LncRNA) is a novel class of functional long RNA molecules that regulate multiple biological functions through various mechanisms. Studies in the past decade have shown that lncRNAs may play an important role in regulating insulin resistance and the progression of T2D. As a widely used biguanide drug, metformin has been used for glucose lowering effects in clinical for more than 60 years. For diabetic therapy, metformin reduces glucose absorption from the intestines, lowers hepatic gluconeogenesis, reduces inflammation, and improves insulin sensitivity. However, despite being widely used as the first-line oral antidiabetic drug, its mechanism of action remains largely elusive. Currently, an increasing number of studies have demonstrated that the anti-diabetic effects of metformin were mediated by the regulation of lncRNA. Metformin-regulated lncRNAs were shown to participate in inhibition of gluconeogenesis, regulation of lipid metabolism, and anti-inflammatory. Thus, this review focuses on the mechanisms of action of metformin in regulating lncRNAs in diabetes, including metformin-altered pathways by targeting lncRNAs, and potential targets of metformin by modulation of lncRNA. Knowledge of the mechanisms of lncRNA modulation by metformin in diabetes will aid the development of new therapeutic drugs for T2D in the future.